Anomalous random telegraph noise and temporary phenomena in resistive random access memory. (November 2016) - Puglisi, Francesco Maria; Larcher, Luca; Padovani, Andrea; Pavan, Paolo
Abstract: In this paper we present a comprehensive examination of the characteristics of complex Random Telegraph Noise (RTN) signals in Resistive Random Access Memory (RRAM) devices with TiN/Ti/HfO2 /TiN structure. Initially, the anomalous RTN (aRTN) is investigated through careful systematic experiment, dedicated characterization procedures, and physics-based simulations to gain insights into the physics of this phenomenon. The experimentally observed RTN parameters (amplitude of the current fluctuations, capture and emission times) are analyzed in different operating conditions. Anomalous behaviors are characterized and their statistical characteristics are evaluated. Physics-based simulations considering both the Coulomb interactions among different defects in the device and the possible existence of defects with metastable states are exploited to suggest a possible physical origin of aRTN. The same simulation framework is also shown to be able to predict other temporary phenomena related to RTN, such as the temporary change in RTN stochastic properties or the sudden and iterative random appearing and vanishing of RTN fluctuations always exhibiting the same statistical characteristics. Results highlight the central role of the electrostatic interactions among individual defects and the trapped charge in describing RTN and related phenomena.